Development of Interactive Video Media to Improve Skill in Writing Simple Sentences of Serang Java Language Local Content Subjects - Uyu Mu'awanah; Rifiq Rizal; Murtafiah Murtafiah; M Syahbudin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to develop interactive video media to enhance the ability of fourth-grade students at a state elementary school in Serang City to write simple sentences. Researchers utilized the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) as outlined by Robert Maribe Branch in a Research and Development (RD) framework. The study involved trials with fourth-grade students using the developed interactive video media. The trials were conducted to gather responses from the students as users of the learning media. The validation assessment by media experts scored 165 with a 94.3% rating in the "Decent" category, while material experts gave a score of 89 with an 89% rating in the same category. The small group trial received a score of 267 with an 83.4% rating, and the field trial scored 641 with an 80.12% rating, both categorized as "Decent." The pretest and posttest results, analyzed using the N-Gain formula, showed an average score of 0.5 with a 100% rating in the "Medium" category. The findings indicate that the developed interactive video media, incorporating local Javanese Banten language content, effectively improves student learning outcomes in fourth-grade elementary school students. Interactive video media is a suitable tool for enhancing sentence writing skills among fourth-grade students at the elemenatary school, demonstrating significant improvements in their learning outcomes.